INTEGRATED RISK MANAGEMENT PROCESS TO MEET HIGH LEVEL OF ATM PROVISION - Lazorenko, Vitaliy; Sukhorebra, Katerina (Proceedings of National Aviation University (archive), 2012)
The definition of risk has been introduced. The structure of Risk Management has been described in details. Strategies of risk control and mitigation have been analyzed. Integrated Risk Management has been described. Risk Management calculation as well as tools and methods have been proposed.